2008
DOI: 10.1364/oe.16.009507
|View full text |Cite
|
Sign up to set email alerts
|

High-power linearly-polarized operation of a cladding-pumped Yb fibre laser using a volume Bragg grating for wavelength selection

Abstract: In this work a volume Bragg grating is used as a wavelength selective element in a high-power cladding-pumped Yb-doped silica fiber laser. The laser produced 138 W of linearly-polarized single-spatial-mode output at 1066 nm with a relatively narrow linewidth of 0.2 nm for approximately 202 W of launched pump power at 976 nm. The beam propagation factor (M(2)) for the output beam was determined to be 1.07. Thermal limitations of volume Bragg gratings are discussed in the context of power scaling for fiber laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Efficient applications of VBGs for stabilizing and narrowing the laser diodes [14], optical parametric oscillators [15] and solid-state lasers [16] have been frequently demonstrated in past years. More recently, VBGs have also been successfully employed as a wavelength selective element in high-power fiber lasers operating in various spectral regions, such as Yb-doped fiber lasers at ~1 μm [17], Er,Yb co-doped fiber lasers at ~1.5-1.6 μm [18][19], Raman fiber lasers at ~1.7 μm [20] and Tm-doped fiber laser at ~2 μm [21] with output powers up to 138 W, 103 W, 11 W and 112 W, respectively. However, to the best of our knowledge, the wavelength narrowing and selection potential of VBGs in the 2.6-5 μm mid-IR wavelength region has not been reported yet.…”
Section: +mentioning
confidence: 99%
“…Efficient applications of VBGs for stabilizing and narrowing the laser diodes [14], optical parametric oscillators [15] and solid-state lasers [16] have been frequently demonstrated in past years. More recently, VBGs have also been successfully employed as a wavelength selective element in high-power fiber lasers operating in various spectral regions, such as Yb-doped fiber lasers at ~1 μm [17], Er,Yb co-doped fiber lasers at ~1.5-1.6 μm [18][19], Raman fiber lasers at ~1.7 μm [20] and Tm-doped fiber laser at ~2 μm [21] with output powers up to 138 W, 103 W, 11 W and 112 W, respectively. However, to the best of our knowledge, the wavelength narrowing and selection potential of VBGs in the 2.6-5 μm mid-IR wavelength region has not been reported yet.…”
Section: +mentioning
confidence: 99%
“…Some numerical calculations on how VBGs are affected by absorption are available in the literature [18][19][20][21]. For a reflected laser beam Jelger et al [18] showed that the heat distribution loosely follows the intensity distribution in the grating for a highly reflective VBG with an absorption coefficient of 10 −3 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Another free space stabilization element is a volume grating written in photo-thermal refractive (PTR) glass, forming a VBG. VBGs have performed well for oscillator stabilization to powers >100 W for Yb, Er: Yb, and Tm oscillators [2][3][4]. In this paper we use a new component known as a guided mode resonance filter (GMRF), which can be produced in large quantities using thin film fabrication techniques.…”
Section: Introductionmentioning
confidence: 99%